2010
DOI: 10.4061/2010/983503
|View full text |Cite
|
Sign up to set email alerts
|

Structural Aspects of Phenylalanylation and Quality Control in Three Major Forms of Phenylalanyl-tRNA Synthetase

Abstract: Aminoacyl-tRNA synthetases (aaRSs) are a canonical set of enzymes that specifically attach corresponding amino acids to their cognate transfer RNAs in the cytoplasm, mitochondria, and nucleus. The aaRSs display great differences in primary sequence, subunit size, and quaternary structure. Existence of three types of phenylalanyl-tRNA synthetase (PheRS)—bacterial (αβ)2, eukaryotic/archaeal cytosolic (αβ)2, and mitochondrial α—is a prominent example of structural diversity within the aaRSs family. Although archa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The values are means of three biological replicates ± SE. misacylation of m-tyrosine (Klipcan et al, 2009;Klipcan et al, 2010), the proteomic data indicated that Phe ! m-Tyr/Tyr exchanges occur more frequently during the synthesis of organellar proteins, and in particularly of those translated within the chloroplasts (Table 3 and Supplementary Data File 1).…”
Section: Analysis Of M-tyrosine Incorporation Into the Plant Proteomementioning
confidence: 99%
See 1 more Smart Citation
“…The values are means of three biological replicates ± SE. misacylation of m-tyrosine (Klipcan et al, 2009;Klipcan et al, 2010), the proteomic data indicated that Phe ! m-Tyr/Tyr exchanges occur more frequently during the synthesis of organellar proteins, and in particularly of those translated within the chloroplasts (Table 3 and Supplementary Data File 1).…”
Section: Analysis Of M-tyrosine Incorporation Into the Plant Proteomementioning
confidence: 99%
“…In plants, the attachment of phenylalanine to tRNA Phe is catalyzed by two major forms of PheRSs. These include i) a heterotetrameric (2•ab) form, which is structurally related to the bacterial 2•ab enzymes and acts in the cytosol, and ii) a degenerated monomeric form (contains fragments of a and b), which dually functions in the plastid and mitochondria of plants (Duchêne et al, 2005;Klipcan et al, 2010).…”
Section: Misincorporation Of Free M-tyrosine Into the Proteome Of Aramentioning
confidence: 99%
“…As direct mediators of translational fidelity, aminoacyl-tRNA synthetases (aaRS) are responsible for the correct pairing of an amino acid with its cognate tRNA [2]. Phenylalanyl-tRNA synthetase (PheRS), for example, is responsible for pairing phenylalanine (Phe) with tRNA Phe [3]. Mispaired aminoacyl-tRNA (aa-tRNA) species occasionally arise due to a lack of adequate amino acid discrimination within the PheRS active site, resulting in the synthesis of misacylated Tyr-tRNA Phe [4].…”
Section: Introductionmentioning
confidence: 99%
“…Mispaired aminoacyl-tRNA (aa-tRNA) species occasionally arise due to a lack of adequate amino acid discrimination within the PheRS active site, resulting in the synthesis of misacylated Tyr-tRNA Phe [4]. The ability of PheRS to misacylate tRNA Phe with non-cognate amino acid makes tRNA proofreading mechanisms of PheRS essential to maintaining the accuracy of translation [3,5]. …”
Section: Introductionmentioning
confidence: 99%
“…21 While heterotetrameric (α 2 β 2 ) form is the most complex among the aaRSs family, monomeric organellar PheRS is the smallest that exhibits aminoacylation activity (Figure 1). 7 Multiple sequence alignment shows that archaeal/eukaryotic cytosolic PheRS (ctPheRS) have originated from a single ancestor, while eubacterial PheRS is thought to be the predecessor of monomeric organellar PheRS. 22 Heterotetrameric PheRS (α 2 β 2 ): structural insight…”
Section: Structural Diversity Of Phersmentioning
confidence: 99%